DECONSTRUCTION TOWARDS ISLAMIC INHERITANCE LAW IN INDONESIA (A Brief Study on Hazairin’s Bilateral Inheritance Idea) - Nasution, Muhammad Amin (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Abstraction Islamic law, especially its socio-cultural realm, has been changing accorded to the local necessities since the very beginning. Umar ibn Khattab, the second successor of Prophet Muhammad peace be upon him, even had ever decided a different jurisprudence to the taken for granted regulations of Hudud at stealing case which was done by his settler. This case has tried to show us that Islamic law deeply prioritized to the justice delivery to the human being. Similar to that case, the Islamic inheritance law has undergone the same situation, even, since the Dutch colonial government. Later on, based on justice delivery consideration which is the inner side of Islamic teaching, some outstanding experts on law such as Hazairin and Munawir Syadzali began to question that matter. This short writing elaborates Hazairin’s deconstructive and controversial idea of Islamic bilateral inheritance and at the same time points out his reliable arguments and methods related to his controversial idea.